Development of management information system for cooperative education in Thailand - Sirikorn Santirojanakul (2018)
© 2018 IEEE. The university-industry-government linkage should drive diverse policies with agility leading to the satisfactory of the requirements. However, the amount of information exceeds the processing capacity of the current system. This paper aims to propose a management information system called Cooperative Education Management System (CEM). The process of CEM is to gather the data from university and produce the real time summary report to the executive body. Moreover, CEM also eliminates wastes, unnecessary processes, in the operation with 50% and 64.7 % for reducing the operation time. In addition, the overall satisfaction of CEM is 4.38.